Evaluation of Experimental Vaccination Against Newcastle Disease in Lovebirds (Agapornis roseicollis): Investigation of the State of Virus Carrier - Martins, Gislaine Regina Vieira; Schmidt , Elizabeth Moreira dos Santos; Carrasco, Adriano Torres; Paulillo, Antonio Carlos; Denadai, Janine (International Journal of Poultry Science, 2011)
The aim of this study was to evaluate the importance of vaccination against Newcastle Disease (ND) in lovebirds (Agapornis roseicollis) and to investigate the state of carrier of the virus (NDV) in this species. There were used 48 lovebirds, distributed at random into 4 experimental groups: GI (Ulster 2C strain), GII (B1 strain), GIII (LaSota strain) and GIV (non-vaccinated group). At 12 months of age, all groups were challenged with a pathogenic virus (NDV) suspension (EID50 = 108.15/0.1 mL) and a group of Specific-Pathogen-Free (SPF) chicks were used as control of the virus. Cloacal swabs from each bird were collected after 9, 14 and 21 days post-challenge for detection of genome viral excretion by Reverse Transcription Polymerase Chain Reaction RT-PCR. Lovebirds of GI, GII and GIII did not demonstrate any signs of ND. They were refractory to the clinical disease. In lovebirds from the control group, NDV genome was detected 9 and 21 days after challenge. Therefore it was demonstrated the state of carrier of NDV by lovebirds. In birds from the vaccinated groups, genome viral excretion was not detected by RT-PCR. It was also demonstrated the importance of the vaccination in the suppression of the state of virus carrier of ND in lovebirds.